Role of CBC and antioxidants for the diagnosis of acute appendicitis in paediatric patients - Abdul Rahman Abid, Muhammad Musab Shah, Siddiqa Batool, Farhan Ali, Naheed Akhtar, Muhammad Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Globally, acute appendicitis (AA) is a common surgical emergency with a lifetime risk of 1 in 7, which means that 6% of the individuals suffer an attack during their lifetime. Objectives: The main objective of the study is to find the role of CBC and antioxidants for the diagnosis of acute appendicitis in paediatric patients. Material and methods: This cross sectional study was conducted in LGH during October 2021 to March 2022. Both male and female patients between the ages of 2 and 16 years and with paediatric appendicitis score (PAS) greater than 4 included in this study. For this purpose, we recorded their age and gender using the hospital information management system database. Results: The data was collected from 38 patients of which 7 (18.4%) were male and 31 (81.6) were female. The mean and standard deviation of age in years was 12.5789 ± 3.10 years. Table 01 shows the frequency of findings of 38 patients. Conclusion: It is concluded that children with acute appendicitis do not have deficient blood plasma antioxidant capacity.